Analysis of Financial Accountability in the Perspective of PSAK Number 45 for Accountability of Financial Reports at Elementary Madrasahs in Tebing Syahbandar District - Mutiara Annisa Damanik; Bi Rahmani, Nur Ahmadi; Harmain, Hendra (Universitas Muhammadiyah Pontianak, 2026)
This study examines financial accountability in Madrasah Ibtidaiyah based on PSAK No. 45. It aims to analyze implementation practices and evaluate their impact on reporting quality. A qualitative method was applied through interviews, observation, and documentation at MIS Rohani Ikhwanul Muslimin. Findings reveal that financial management is relatively transparent but reporting remains limited to simple income–expense records and does not fully comply with PSAK No. 45 components. Constraints include limited human resources and accounting knowledge. The study implies that strengthening capacity and adopting standardized reporting can improve transparency, accountability, and stakeholder trust.